PROBABILITAS RISIKO TERKENA PENYAKIT JANTUNG DAN TB BERDASARKAN FAKTOR SOSIO-EKONOMI DAN DEMOGRAFI - Tarani, Ni Putu Mia; Kautsar, Achmad (Jurnal Ekonomi Kesehatan Indonesia, 2022)
This study aims to examine the effect of socioeconomic status and demographics on the probability of health status represented by heart disease and tuberculosis (TB). This study uses data from the Indonesian Family Life Survey (IFLS), an ongoing longitudinal survey in Indonesia. There are several independent variables in this study such as the amount of cigarette consumption, nutritional status and also blood pressure, with marginal effects as a measure of the relationship. In this study there are two dependent variables, namely heart disease and TB with the same independent variables, this is done to measure and compare how much influence the independent variables have on the two models of the dependent variable. The number of observations in this study were 8,895 individuals. This study found that socioeconomic factors such as education level had a significant positive effect on an individual's risk of developing heart disease and TB. Individuals who are categorized as poor do not significantly affect the probability of a person's risk of suffering from heart disease by 0.13 percent and TB by 0.33 percent. Various other factors such as nutritional status and blood pressure also have an influence on the risk of heart disease and TB.